Formal Gardens, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Park, A.J. (1909)
Caption on image: Formal Gardens. A.Y.P.E. 1909. PH Coll 777 Park.4 (See also PH Coll 78.148) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number